Internalisasi Nilai-nilai Religi pada Usia Dini dalam Menyongsong Generasi Emas yang Islami - Ni'mah, Zetty Azizatun (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
The successful of a religious personality is through the child's learning needs to be supported by the exemplary elements from both teachers and parents. For the purpose of the implementation can be done in a gradual learning strategies and develop habituation program or daily activities. To implement the program of religious values, teachers must be constantly creative and innovating to use a variety of approaches in accordance with the level of development and students' needs, a comprehensive curriculum, and the continuity between the development program with other programs. The presence of the curriculum in 2013 with a science characteristic (observe, ask, explore, associate, communicate) and authentic assessment have to be understood early childhood teachers so that the internalization of religious values ​​can be absorbed in the learning process. Each children must has expected to be a good boy who obey the religious values. Early Childhood Education as an institution that expectedly nurturing children in a golden age.